Effects of employees' opportunities to influence in-store music on sales: Evidence from a field experiment - Sven-Olov Daunfeldt; Jasmine Moradi; Niklas Rudholm; Christina Öberg (Institute of Retail Economics (HFI), 2019)
The effects of in-store music on consumer behavior have attracted much attention in the marketing literature, but surprisingly few studies have investigated in-store music in relation to employees. Conducting a large-scale field experiment in eight Filippa K fashion stores in Stockholm, Sweden, we investigate whether it is beneficial for store owners to give employees more opportunities to influence the in-store music. The experiment lasted 56 weeks, and the stores were randomly assigned into a treatment group and a control group, with the employees in the treatment stores having the opportunity to influence the in-store music through an app developed by Soundtrack Your Brand (SYB). The results from the experiment show that sales decreased by, on average, 6% in treatment stores when employees had the opportunity to influence the music played in the store. Interviews revealed that employees frequently changed songs, preferred to play high-intensity songs, and had diverse music preferences that were not congruent with the brand values of the company. Our results thus imply that employees choose music that suits their preferences rather than based on what is optimal for the store, suggesting that store owners might want to limit their opportunities to influence the background music in stores.
Keywords: C93; D22; L81; M31; M54; 330; Background music; Brand-fit music; Music tempo; Consumer behavior; Job satisfaction; Atmospheric cues; Work environment; Field experiment